(untitled) (Journal of Engineering, 2022)
These days, the world is facing a global environmental and sustainability problem due to the increasing generation of large amounts of waste through construction and demolition work, which causes a serious problem for the environment. Therefore, this research was conducted to get rid of the waste disposal problems, including old glass and concrete, which were used as recycled fine aggregates. Seven different mixtures were prepared. The first mixture was with the used sand, which is glass sand, and it was adopted as a reference mixture (ORPC), and three mixtures were prepared for each of the recycled materials (waste concrete and glass) and partially replaced by glass sand in different proportions (25, 50, and 75) %. Some mechanical properties, including compressive strength and flexural strength, were determined and tested at the age of (14, 28, and 90) days. Samples were processed at 20°C and heat treated at 90°C for 90 days. The results showed that the resistance reductions increased with the increase in the percentage of recycled fine aggregate, and the best replacement ratio is 25% for both materials used from waste concrete and glass.